Guidance and Science Skills for Street Children - Sari, Eza Permata; Fatmariza; Montesossori, Maria; Syafrini, Delmira (Jurnal Penelitian Pendidikan IPA, 2024)
Various programs were developed in response to the street children problem in Indonesia. The government (social services) has implemented a policy to overcome the problem of street children in the city of Jambi, including creating a shelter home policy for street children to study and provide skills in the field of science. This research aims to determine the effectiveness of skills in the field of science in handling street children. This research uses empirical demonstration and juridical methods using research specifications, population, samples, informants, data collection, data processing, and analysis. The results of the research show that skills in the field of science are very effective in developing street children in the city of Jambi, although they have not optimally reduced the number of street children in the city of Jambi due to several factors, both internal and external.